Arid Lands Water Evaluation and Management - Maliva, Robert; Missimer, Thomas; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
A large part of the global population lives in arid lands which have low rainfall and often lack the water required for sustainable population and economic growth. This book presents a comprehensive description of the hydrogeology and hydrologic processes at work in arid lands. It describes the techniques that can be used to assess and manage the water resources of these areas with an emphasis on groundwater resources, including recent advances in hydrologic evaluation and the differences between how aquifer systems behave in arid lands versus more humid areas. Water management techniques are described and summarized to show how a more comprehensive approach to water management is required in these areas, including the need to be aware of cultural sensitivities and conditions unique to many arid regions. The integration of existing resources with the addition of new water sources, such as desalination of brackish water and seawater, along with reusing treated wastewater, will be required to meet future water supply needs. Also, changing climatic conditions will force water management systems to be more robust so that future water supply demands can be met as droughts become more intense and rainfall events become more intense. A range of water management techniques are described and discussed in order to illustrate the methods for integrating these measures within the context of arid lands conditions.
From the Contents: Aridity and Drought -- Geology of Arid Lands -- Aquifer Concepts in Arid Lands -- Introduction to Aquifer Hydraulics -- Water Budget -- Precipitation and Evapotranspiration -- Recharge Concepts and Settings -- Sustainability and Safe Yield -- Assessment of Groundwater Resources -- Recharge Measurement in Arid and Semiarid Regions -- Environmental Isotopes -- Wadi Recharge Evaluation -- Microgravity -- Compaction and Land Subsidence -- Surface and Airborne Geophysics -- Borehole Geophysical Techniques -- Remote Sensing -- Geographic Information Systems -- Groundwater Flow and Solute-Transport Modeling -- Ancient Water Management -- Rainwater, Stormwater, and Fog Harvesting -- Managed Aquifer Recharge.
Keywords: Geography; Hydraulic engineering; Environmental pollution; Earth Sciences; Environmental Science and Engineering; Hydrogeology; Waste Water Technology / Water Pollution Control / Water Management / Aquatic Pollution